Oral health beliefs, knowledge, and behaviors in Northern California American Indian and Alaska Native mothers regarding early childhood caries. (27th April 2017) - Heaton, Brenda; Crawford, Andrew; Garcia, Raul I.; Henshaw, Michelle; Riedy, Christine A.; Barker, Judith C.; Wimsatt, Maureen A.; ,
Abstract: Objectives: To assess the oral health beliefs, knowledge, and behaviors related to early childhood caries (ECC) risk in a convenience sample of American Indian and Alaska Native (AIAN) mothers residing in rural Northern California communities. Methods: Fifty‐three mothers of young children were recruited from three tribal communities in Northern California with the assistance of the California Rural Indian Health Board, Inc. and its California Tribal Epidemiology Center and Dental Support Center. Trained study staff administered questionnaires to obtain basic socio‐demographic information, to survey participants on their oral health beliefs, knowledge, and behaviors as related to ECC risk, and to identify possible barriers to their accessing professional oral health care. Analyses of covariance were used to explore associations between socio‐demographic indicators and oral health behaviors, after controlling for knowledge, beliefs and barriers to care. Results: Overall, 53 percent of participants reported their oral health as "fair" or "poor." Mothers' education (high) and being employed were positively associated with better oral health behavior scores. Additionally, 72 percent of mothers reported having one or more barriers to oral health care including access. There was a significant relation ( P  = 0.03) between high number of reported barriers to oral health care and low oral health behavior scores. Conclusions: Despite generally high‐level oral health knowledge, perceptions of self and child oral health remains low in this sample of AIAN mothers. Factors identified as being associated with oral health behaviors in this sample were similar to those found in other health disparities populations.